A toxicological assessment of Ganoderma lucidum and Cordyceps militaris mushroom powders - Chrysostomou, Paola P.; Freeman, Elaine; Murphy, Mary M.; Chaudhary, Ankit; Siddiqui, Nazia; Daoust, Julie (Frontiers in Toxicology, 2024)
Gonoderma lucidum (G. lucidum) and Cordyceps militaris (C. militaris) are among the many mushrooms known for their long history of use in traditional medicine. Wildcrafted sources of mushrooms including G. lucidum and C. militaris can be limited from a scarcity and quality perspective, but solid fermentation processes in cultivation settings can provide an efficient way to deliver whole mushroom preparations of a consistent composition. Despite the historical use of these mushrooms, few published reports have explored their potential subchronic oral toxicity or genotoxicity, either from specific components or whole mushroom preparations. The purpose of this study was to assess the potential for acute toxicity, subchronic toxicity, and genotoxicity of powders produced from G. lucidum mycelial biomass and fruiting body (“Organic Reishi M2-102-02 powder”) cultured on oats, and C. militaris mycelial biomass, stroma, and fruiting body (“Organic Cordyceps M2-116-04 powder”) cultured on oats. Results of the testing demonstrate that both Organic Reishi M2-102-02 powder and Organic Cordyceps M2-116-04 powder were not acutely toxic, did not exhibit subchronic oral toxicity in rats at doses up to the highest dose tested of 2,000 mg/kg bw/day, and did not have genotoxic potential based on in vitro and in vivo genotoxicity assays.